To the issue of the pilot legal regime on telemedicine technologies - Platonova, Natalya I. (Journal of the Belarusian State University. Law, 2021)
The article is devoted to the study of the Russian health care system’s digitalisation. The results of the digital maturity research of the Russian regions, as well as the analyses of a current problems of the health care system shows the risk of reduced access to health care. The wide use of telemedicine technologies could help to solve these problems partly. Current legislation, however, did not allow for adequate use of telemedicine. In that connection, it would be interesting to consider the possibility of introducing a pilot legal regime for telemedicine technologies, as well as the attendant risks of such regimes. It is important that the experimental legal regime for telemedicine to be established by the end of this year be based not only on the principles specified in the relevant law, but also on the principle of reasonableness, and necessity, and the priority of the patient’s rights and legitimate interests.
Keywords: health care system; digital maturity; pilot legal regime; telemedicine technologies; medical assistance; digitalisation